Geometric Controls on Tidewater Glacier Retreat in Central Western Greenland. Issue 8 (30th August 2018) - Catania, G. A.; Stearns, L. A.; Sutherland, D. A.; Fried, M. J.; Bartholomaus, T. C.; Morlighem, M.; Shroyer, E.; Nash, J.
Abstract : Glacier terminus changes are one of the hallmarks of worldwide glacier change, and thus, there is significant focus on the controls and limits to retreat in the literature. Here we use the observational record of glacier terminus change from satellite remote sensing data to characterize glacier retreat in central West Greenland with a focus on the last 30 years. We compare terminus observations of retreat to glacier/fjord geometry from available bed and bathymetry data and find that glacier retreat accelerates through wide, overdeepened parts of the bed characterized by retrograde bed slopes. We find that the morphology of the overdeepening can be used as a predictive measure for the length of retreat and that short regions (less than twice the seasonal change in terminus position) of the bed with prograde bed slopes are not sufficient to stop a retreating terminus. Even narrow overdeepenings can control glacier retreat, likely because they focus subglacial runoff, which entrains warm water in the fjords when it emerges at the grounding line and melts the terminus, creating enhanced local retreat. Future retreat of these glaciers is assessed given upstream fjord geometry. Plain Language Summary: Glaciers that reach the marine margin of the Greenland Ice Sheet are experiencing increases in mass loss over time. These losses are greater than land‐terminating glaciers and are spatially variable. Even glaciers that drain into the same fjord system can experience different amounts, rates, and durations of retreat and thinning. To explain this, we examined retreat over an ∼30‐year record derived from satellite images of Greenland and compared it to the submarine fjord and subglacial topography across a region containing 15 glaciers. We find good correspondence between glacier retreat and the length of an overdeepened reach of the fjord behind the glacier terminus. Key Points: Glacier termini in central West Greenland began progressive retreat in 1998 +/‐3 years Heterogeneous retreat rates and extents can be partially explained by local differences in bed topography Length of overdeepening behind the terminus controls the amount of retreat observed